Identification of regulatory elements required for Stra8 expression in fetal ovarian germ cells of the mouse - Feng, Chun-Wei; Burnet, Guillaume; Spiller, Cassy M; Cheung, Fiona Ka Man; Chawengsaksophak, Kallayanee; Koopman, Peter; Bowles, Josephine (Development (Cambridge), 2021)
In mice, the entry of germ cells into meiosis crucially depends on the expression of stimulated by retinoic acid gene 8 ( ). is expressed specifically in pre-meiotic germ cells of females and males, at fetal and postnatal stages, respectively, but the mechanistic details of its spatiotemporal regulation are yet to be defined. In particular, there has been considerable debate regarding whether retinoic acid is required, , to initiate expression in the mouse fetal ovary. We show that the distinctive anterior-to-posterior pattern of initiation, characteristic of germ cells in the fetal ovary, is faithfully recapitulated when 2.9 kb of the promoter is used to drive eGFP expression. Using transfection assays of cutdown and mutant constructs, we identified two functional retinoic acid responsive elements (RAREs) within this 2.9 kb regulatory element. We also show that the transcription factor DMRT1 enhances expression, but only in the presence of RA and the most proximal RARE. Finally, we used CRISPR/Cas9-mediated targeted mutation studies to demonstrate that both RAREs are required for optimal expression levels .